Revalidation of game for teaching blood pressure auscultatory measurement: a pilot study - Margarete Consorti Bellan; Vanessa Cortez Alves; Mayza Luzia dos Santos Neves; José Luiz Tatagiba Lamas
ABSTRACT Objective: To adapt a pre-existing educational game, making it specific to the teaching of blood pressure auscultatory measurement, and to apply this game in a pilot study. Method: The original game cards were altered by the authors and submitted to content validation by six experts in the field. After redesigns, the game was applied to 30 subjects, who answered a questionnaire (pre-test and post-test) on auscultatory measurement. Data were analyzed descriptively and by the paired Student's t-test and paired Wilcoxon test. Results: Throughout the content validation process, 17 of the 28 original cards were modified. Of these 17 cards, 13 obtained 80% agreement, and the rest were modified according to the judges' suggestions. The obtained grades significantly increased between pre- and the post-test. Conclusion: It was concluded that the reformulated game presented satisfactory evidence of content validity. Its use as a teaching-learning method was effective for this sample.